ANALISIS EKONOMI MESIN PENGOLAH NIRA AREN MENJADI GULA SEMUT DI KELOMPOK TANI KARYA TANI DI DESA TALAITAD - Nikita V. Momongan; Robert Molenaar; Esry O. H. Laoh (COCOS, 2021)
AbstractThe purpose of this study is to analyze the economy, total costs and economicfeasibility of the of palm sugar processing machine HORJA MPN20 concerning the total costof processing, and economic feasibility is assessed from 4 criteria, namely: BEP, NPV, B/CRATIO, and IRR used by farmer groups in Talaitad Village, Suluun Tareran Subdistrict,South Minahasa Regency. The results showed an analysis of the operational feasibility of sappalm into palm sugar based on the amount of potential services available and using the basisof commercial business scale calculation resulted in a Net Present Value (NPV) ofRp.153,130,851.72, Internal Rate of Return (IRR) of 97%, Benefit/Cost Ratio (B/C Ratio) of1.32 and Break Even Point of operation of palm sugar processing machine MPN20 are at anoperating rate of 116.50kg/year or equivalent to Rp.4,653,142.02/year.Key words: economics analysis, palm sugar, processing machine of palm sugar